Long-term administration of alendronate sodium caused an atypical femoral shaft fracture in a 36-year-old woman: a case report and literature review - Wenyu Duan; Maochang Qiang; Haidong Zhang; Dongming Zhou (Journal of International Medical Research)
Long-term bisphosphonate therapy is associated with atypical or insufficiency fractures, particularly in the proximal femur. We observed a case of an atypical femoral shaft fracture in a patient with a long-term history of alendronate therapy. A 36-year-old woman was admitted with a complaint of pain in her right mid-thigh following low-energy trauma. She had been taking alendronate for more than 15 years. X-rays indicated a fracture of the right femoral shaft. The patient was treated with proximal femoral nail antirotation (PFNA) fixation. This case highlights concerns regarding long-term bisphosphonate therapy and its potential complications.